FACTORS INFLUENCING ENVIRONMENTAL FRIENDLY PRODUCT CONSUMPTION CONSCIOUSNESS IN KARAWANG - Syahrivar, Jhanghiz; Rizky, Mega (Manajemen Bisnis Kompetensi, 2017)
ABSTRACT:In order to protect the environment from the adverse impact of a business and irresponsible consumption, more and more local leading and multinational companies in Indonesia come up with a so called environmental friendly product. However, the market share of an environmental friendly product is normally that below the market shares of conventional products due to various factors. This research was aimed to analyze factors influencing consumption consciousness of environmental friendly product in Karawang, one of the most polluted cities (regencies) according to some sources. Several identified factors were Environmental Knowledge, Religiosity, Economic Factors, and Government Role that were hypothesized to influence Environmental Friendly Product Consumption Consciousness. The researchers collected 250 respondents as samples using both online and offline questionnaires. Structural Equation Modelling was utilized in this research to test the hypotheses. The findings suggested that Environmental Knowledge and Economic Factors were significantly influencing Environmental Friendly Product Consumption Consciousness. Keywords: Environmental Knowledge, Religiosity, Economic Factors, Government Role, Environmental Friendly Product Consumption Consciousness, Structural Equation Modelling.ABSTRAK:Untuk melindungi lingkungan dari dampak buruk suatu proses bisnis dan konsumsi yang tidak bertanggung jawab, semakin banyak perusahaan terkemuka dan multinasional lokal di Indonesia menghasilkan produk ramah lingkungan. Namun, pangsa pasar produk ramah lingkungan biasanya berada di bawah pangsa pasar produk konvensional karena berbagai faktor. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi kesadaran konsumsi produk ramah lingkungan di Karawang, salah satu kabupaten paling berpolusiÃÂ  menurut beberapa sumber. Beberapa faktor yang diidentifikasi adalah Pengetahuan Lingkungan, Religiusitas, Faktor Ekonomi, dan Peran Pemerintah yang dihipotesiskan mempengaruhi Kesadaran Konsumsi Produk Ramah Lingkungan. Para peneliti mengumpulkan 250 responden sebagai sampel dengan menggunakan alat bantu kuisioner, baik secara tatap muka langsung maupun secara online. Pemodelan Persamaan Struktural digunakan dalam penelitian ini untuk menguji hipotesis. Temuan menunjukkan bahwa Pengetahuan Lingkungan dan Faktor Ekonomi secara signifikan mempengaruhi Kesadaran Konsumsi Produk Ramah Lingkungan.Kata kunci: Pengetahuan Lingkungan, Religiusitas, Faktor Ekonomi, Peran Pemerintah, Kesadaran Konsumsi Produk Ramah Lingkungan, Pemodelan Persamaan Struktural.